Galanin and Adrenomedullin Plasma Responses During Artificial Gravity on a Human Short-Arm Centrifuge - Winter, Julia; Laing, Charles; Johannes, Bernd; Mulder, Edwin; Brix, Bianca; Roessler, Andreas; Reichmuth, Johannes; Rittweger, Joern; Goswami, Nandu (Frontiers in Physiology, 2019)
Galanin and adrenomedullin plasma responses to head-up tilt and lower body negative pressure had been studied previously. However, to what extent by short-arm human centrifugation (SAHC) affects these responses is not known. In this study, we assessed how the application of variable gradients of accelerations (Δgz) via shifting of the rotation axis during centrifugation affects selected hormonal responses. Specifically, we tested the hypothesis, that cardiovascular modulating hormones such as galanin and adrenomedullin will be higher in non-finishers when compared to finishers during SAHC exposure. Twenty healthy subjects (10 women and 10 men) were exposed to two g-levels (1gz and 2.4gz at the feet (gz_Feet)) in two positions (axis of rotation placed above the head and axis of rotation placed at the heart’s level). Subjects were categorized as finishers or non-finishers based on whether presyncopal signs developed before protocol completion. Elevated baseline levels of galanin appeared to predict orthostatic tolerance (p=0.054) and seemed to support good orthostatic tolerance during 1 gz_Feet SAHC (p=0.034). In finishers, 2.4 gz_Feet SAHC was associated with increased galanin levels after centrifugation (p=0.007). For adrenomedullin, the hypothesized increases were observed after centrifugation at 1 gz_Feet (p=0.031), but not at 2.4 gz_Feet, suggesting that other central mechanisms than local distribution of adrenomedullin predominate when coping with orthostatic challenge (p >0.14). In conclusion, galanin levels increase during elevated levels of central hypovolemia and appear to be important for coping with such challenges. For adrenomedullin, we found that its release depends on degree of central hypovolemia induced fluid shifts and subject’s ability to cope with such challenges. Furthermore, the gradient of acceleration Δgz is shown to be an innovative approach to quantify the grade of central hypovolemia and to assess cardiovascular and neurohormonal responses in those that can tolerate (finishers) or not tolerate (non-finishers) artificial gravity (AG). As AG is being considered as a preventing tool for spaceflight induced deconditioning in future missions, understanding the effects of AG on cardiovascular and hormonal responses in subjects that develop presyncope is important.